Effect of Water Circulation on the Distribution of Zooplankton in the Southern Waters of Peninsular Malaysia - Shafie, Balqis Balqiah; Juneng, Liew; Abdul Rahim, Azman (Jurnal Riset Biologi dan Aplikasinya, 2023)
The waters of Peninsular Malaysia located between the South China Sea and the Straits of Malacca are greatly influenced by two different monsoons: the Southwest Monsoon (SW) and the Northeast Monsoon (NE). Zooplankton are known to be receptive to any environmental changes. Apart from biotic and abiotic changes, the movement of water currents also has an impact on the distribution and composition of zooplankton, as this group is considered a passive swimmer that is dependent on the movement of water currents. This study was conducted to determine the effect of water movement in the southern waters of Peninsular Malaysia on the distribution of zooplankton. Sampling was done in three main areas: Kukup, Pengerang, and Pulau Besar. A total of 16 stations with three replicates per station were performed using a plankton net with a mesh size of 140µm. Results show that zooplankton in Pengerang recorded the highest with 256.157 ind/ m3, followed by Kukup (132.412 ind/m3) and Pulau Besar (54.066 ind/m3). There were seven dominant species of copepods recorded in this study, namely Acrocalanus gracilis, Bestiolona similis, Euterpina acutifrons, Oithona nana, Oithona similis, Paracalanus aculeatus, and Paracalanus denudatus. Generally, this study has shown a notable relationship between local current circulation patterns and zooplankton distribution.